A novel cell cycle-associated lncRNA, HOXA11-AS, is transcribed from the 5-prime end of the HOXA transcript and is a biomarker of progression in glioma. Issue 2 (10th April 2016) - Wang, Qixue; Zhang, Junxia; Liu, Yanwei; Zhang, Wei; Zhou, Junhu; Duan, Ran; Pu, Peiyu; Kang, Chunsheng; Han, Lei
Highlights: HOXA11-AS, a novel lncRNA, is transcribed from the 5-prime end of the HOXA transcript and has an oncogenic function in glioma. HOXA11-AS is a biomarker of progression and potential therapeutic target for glioma. HOXA11-AS promotes gliomagenesis by regulating cell cycle progression. Abstract: The comprehensive lncRNA expression signature in glioma has not yet been fully elucidated. We performed a high-throughput microarray to detect the ncRNA expression profiles of 220 human glioma tissues. Here, we found that a novel lncRNA, HOXA11-AS, was the antisense transcript of the HOX11 gene. It was shown that HOXA11-AS was closely associated with glioma grade and poor prognosis. Multivariate Cox regression analysis revealed that HOXA11-AS was an independent prognostic factor in glioblastoma multiforme patients, and its expression was correlated with the glioma molecular subtypes of the Cancer Genome Atlas. Gene set enrichment analysis indicated that the gene sets most correlated with HOXA11-AS expression were involved in cell cycle progression. Over-expression of the HOXA11-AS transcript promoted cell proliferation in vitro, while knockdown of HOXA11-AS expression repressed cell proliferation via regulation of cell cycle progression. The growth-promoting and growth-inhibiting effects of HOXA11-AS were also demonstrated in a xenograft mouse model. Our data confirms, for the first time, that HOXA11-AS is an important long non-coding RNA that primarily serves as a prognostic factor for glioma patient survival. HOXA11-AS could serve as a biomarker for identifying glioma molecular subtypes and as therapeutic target for glioma patients.